Analysis of Display Cabinet Design with Commissioning Test for Fresh Sea Food - I Dewa Made Cipta Santosa; I Gede Nyoman Suta Waisnawa; I Gusti Agung Bagus Wirajati; I Gede Thio Cahya Dinata; I Komang Raditya Cahya Dinata (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This research is a design of a display cabinet cooling system with integrated energy from PLN electricity and solar power. This equipment is used for displaying marine fish and other fresh sea food in restaurants or cafes in support of Balinese culinary specialties, namely grilled fish and seafood which are very well known and can be a very extraordinary carrying capacity for Bali tourism. This cooling system is designed to be able to maintain the temperature of the cooling room (cabin) up to -5 oC. This is in accordance with the standards for storing fresh sea fish and sea food in a temperature range of -2oC to 2oC, where fish and sea food are still in a very fresh condition for an average of 1 week. Other standards to maintain product freshness also require room humidity between RH 90% – RH 95%. Furthermore, data collection on system performance is carried out using the commissioning test method to determine the initial performance achievement of the tool so that its shortcomings can be evaluated which will be developed and corrected in further research. From the research, it is found that the temperature achievement is very good, the solar and PLN integration system with the Automatic Transfer Switch (ATS) control system has also worked well where the switch occurs when the battery charging condition is below 30% or below 10V. However, something that has not been achieved is the humidity in this system, the average relative humidity (RH) is 50% so that the final condition of the product becomes dry on the surface of the fish. This relatively low humidity is due to the fact that it still relies on the humidity increase system by opening the cooler cabin door. In the next development, the right humidifier system will be designed for this display cabinet system.